2020
DOI: 10.1111/cod.13717
|View full text |Cite
|
Sign up to set email alerts
|

The epidemic of contact allergy to methylisothiazolinone—An analysis of Danish consecutive patients patch tested between 2005 and 2019

Abstract: Background In 2005, methylisothiazolinone (MI) was allowed as a stand‐alone preservative in cosmetics. This resulted in an epidemic of allergic contact dermatitis to MI, mainly affecting women exposed to leave‐on cosmetics. Consequently, a regulation of Annex V in the European Union in 2017 banned the use of MI in leave‐on cosmetics and reduced the allowed concentration in rinse‐off products. Objective To analyze the temporal trends in contact allergy to MI in Danish patients in relation to key events includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 19 publications
1
17
1
Order By: Relevance
“…This epidemic has giving rise to both facial allergic dermatitis and hand dermatitis. [24][25][26][27][28][29] In Denmark, the prevalence of contact allergy to MI significantly increased from 1.5% in 2005 to 5.7% in 2013 where 41% of the patients with MI allergy were affected by FD. 30 A regulation was introduced in 2017 with the purpose of decreasing the prevalence.…”
Section: Database Studymentioning
confidence: 99%
“…This epidemic has giving rise to both facial allergic dermatitis and hand dermatitis. [24][25][26][27][28][29] In Denmark, the prevalence of contact allergy to MI significantly increased from 1.5% in 2005 to 5.7% in 2013 where 41% of the patients with MI allergy were affected by FD. 30 A regulation was introduced in 2017 with the purpose of decreasing the prevalence.…”
Section: Database Studymentioning
confidence: 99%
“…There can be many reasons for this increase in OCD, one of which could be the increasing use of each childcare facility is responsible for buying its own supplies, making it vulnerable to products of more varying quality.In 2017 the use of MI was substantially restricted in the European Union, but as we compare the two periods 2007-2012 and 2013-2018, the consequences of the restriction in the use of MI are not likely to manifest itself in our results. A Danish study from 2020 found a steep incline in the prevalence of MI patch test positivity from 2010 to 2013, and a decline from 2017 to 2019 22.…”
mentioning
confidence: 99%
“…The latter observation might suggest a diminished burden of disease in the most recently diagnosed patients with Cr allergy. However, an increasing level of disease burden in controls might explain the lack of case‐control difference observed which might partly be due to the outbreak of methylisothiazolinone epidemic in 2010, peaking in 2013 14 . The lack of improvement in disease severity over time may also be attributed to the tertiary selection of our study population, hence mainly capturing the most severe cases of Cr allergy.…”
Section: Discussionmentioning
confidence: 94%
“…This study was limited by a relatively short postregulatory observation period, hence possibly not capturing the full effect of regulation. Furthermore, this study was limited by including the transition period (2013‐2014) as part of the postregulatory observation period which might be too soon to expect industrial adaptation despite reports of other regulated allergens showing decreasing trends in sensitization rates among patients with dermatitis years before implementation of an upcoming EU ban 14,21 . Nevertheless, no improvements were found in patients with Cr allergy with regard to severity of disease or dermatitis from leather exposures for other temporal stratifications (data not shown).…”
Section: Discussionmentioning
confidence: 95%